Adaptive QoS Routing by Cross-Layer Cooperation in Ad Hoc Networks. Issue 5 (12th December 2005) - Sun, Hongxia; Hughes, Herman D.
Abstract : QoS provisioning is a complex and challenging issue in mobile ad hoc networks, especially when there are multiple QoS constraints. In this paper, we propose an adaptive QoS routing scheme supported by cross-layer cooperation in ad hoc networks. The cross-layer mechanism provides up-to-date local QoS information for the adaptive routing algorithm, by considering the impacts of node mobility and lower-layer link performance. The multiple QoS requirements are satisfied by adaptively using forward error correction and multipath routing mechanisms, based on the current network status. The complete routing mechanism includes three parts: (1) a modified dynamic source routing algorithm that handles route discovery and the collection of QoS-related parameters; (2) a local statistical computation and link monitoring function located in each node; and (3) an integrated decision-making system to calculate the number of routing paths, coding parity length, and traffic distribution rates. Simulation results are presented to illustrate the overall performance of our scheme. Our results indicate that our adaptive routing scheme provides suitable QoS performance that is less sensitive to network conditions (i.e., node mobility, transmission power, channel characteristics, and the traffic pattern) than a nonadaptive routing strategy.